2009
DOI: 10.1063/1.3062813
|View full text |Cite
|
Sign up to set email alerts
|

Exchange bias of ferromagnetic/antiferromagnetic in FePt/FeRh bilayers

Abstract: A systematic investigation of structural and magnetic properties of FePt/FeRh bilayers has been carried out. The transition temperature of single FeRh layer is higher than that of FePt/FeRh bilayer. A sharp decrease in coercivity is observed at transition temperature for FePt/FeRh bilayer. The thickness FePt dependence of exchange bias field and unidirectional anisotropy constant are discussed. Of interest is the exchange bias effect that appears in FePt/FeRh bilayer and the unidirectional anisotropy constant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…The value of out-of-plane coercivity is around 7 kOe and it is clear that the coupling between FeRh layer and FePt layer is antiferromagnetic/ferromagnetic interaction. Consequently, there is an exchange bias effect in the hysteresis loops at low temperature, as reported in previous studies [10]. It can be seen from Fig.…”
Section: Magnetic Propertiessupporting
confidence: 50%
“…The value of out-of-plane coercivity is around 7 kOe and it is clear that the coupling between FeRh layer and FePt layer is antiferromagnetic/ferromagnetic interaction. Consequently, there is an exchange bias effect in the hysteresis loops at low temperature, as reported in previous studies [10]. It can be seen from Fig.…”
Section: Magnetic Propertiessupporting
confidence: 50%
“…2,3 The existence of this transition just above room temperature (RT)-near 350 K-makes FeRh a unique model system, which is still of significant interest in the physics and materials science community. [4][5][6][7][8][9] It has been proposed as a candidate material for heat-assisted magnetic recording (HAMR), where it would be coupled to ferromagnetic layers, [10][11][12] as well as for magnetocaloric cooling. In most of the thin-film studies, both fundamental and applied, FeRh is capped with a thin film layer to protect against oxidation, commonly a noble metal (Au, Pt) or a light selfpassivating metal such as Al.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Nam et al introduced the FePt alloy film as a FM-layer, which was coupled with FeRh (AFM-layer) for use in PEB systems. 12,13 In 2011, Kosub et al observed the PEB phenomenon at 10 K in CoO/Co 3 Pt bilayers. 14 However, the PEB that is caused by an alloy single-layered thin film with PMA has been rarely examined.…”
mentioning
confidence: 98%